Rocket Motor with Composite Casing - Zbigniew Drabik; Tomasz Rasztabiga (Problemy Mechatroniki)
The article presents the results of work concerning a two-stage rocket motor. In the first step tested stationary the charge rocket motor with the ignitor and the nozzle system in the ballistic chamber was tested. The technology of composite casing with a caliber of 171 mm, which is also a combustion chamber, was designed and mastered. The composite casing was tested stationary in complete rocket motor. The next step was to conduct dynamic tests at the rocket test range. During the dynamic tests a two-stage rocket with a mass of 70 kg was fired. The rocket has reached a maximum speed of 960 m / s.